Learning by sharing in tough times. The Swedish study circle method and its educational hope for migrant adults - Adamczewski, Jakub; Rozvadská, Katarína (Adult Education Discourses, 2022)
The current political and economical world situation does not fill us with optimism. The recent case of migration and forced displacement in Europe due to the war conflict in Ukraine raises questions about the use of methods that can help adult migrants to carry on with their lives in a new country. Our conceptual paper builds on the Swedish history and experience of migration, together with a study circle form of adult education that is popular and valued here. The aim of the article is to describe the educational possibilities for migrant adults by sharing the good practices worked out in Sweden in recent years. This kind of knowledge can be seen as a valuable lesson for those countries that are in need of systemic solutions in regard to forced migration.